2014
DOI: 10.1177/0268355514529699
|View full text |Cite
|
Sign up to set email alerts
|

Venous ulcer care: which dressings are cost effective?

Abstract: Healed or open venous ulcers may be present in up to 1% of Western populations and consume a large amount of healthcare resources. These ulcers are characterized by a chronic inflammatory environment with impaired healing and often require months for closure. The average monthly cost of care for an open ulcer has been estimated to be $4095. The fundamental tenets of ulcer care include adequate compression and maintaining a moist wound environment with an appropriate primary dressing. A number of specialized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“… 9 - 12 These results are similar to those found by authors who have reported that pentoxifylline is a satisfactory adjuvant medication for healing of VU of lower limbs, but the data do not prove its efficacy. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 - 12 These results are similar to those found by authors who have reported that pentoxifylline is a satisfactory adjuvant medication for healing of VU of lower limbs, but the data do not prove its efficacy. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…No entanto, essa redução não teve diferença estatisticamente significativa quando comparados os momentos de avaliação (diagnóstico e após o tratamento) em cada grupo e entre os grupos, apesar de alguns estudos da literatura demonstrarem um efeito positivo significativo da pentoxifilina na cicatrização de úlceras varicosa 9 - 12 . Esses resultados são semelhantes aos encontrados por autores que relataram que a pentoxifilina é uma medicação adjuvante satisfatória na cicatrização das UV de MMII, mas os dados não conseguiram provar a sua eficácia 28 , 29 .…”
Section: Discussionunclassified
“…60 Occlusive hydrocolloid dressings have been found to reduce pain and are often preferred by patients because of this effect, the ease of application, and lower cost. 60 Other types of dressings, such as low adherent dressings, are inexpensive but require frequent changes and they control odor and drainage poorly. Hydrofibers and alginates are highly absorbent and well-suited for management of the heavily draining VLUs.…”
Section: Dressingsmentioning
confidence: 99%